Construire des connaissances sur les pratiques d'enseignement : travail d'objectivation et vigilance épistémologique - Gwénaël Lefeuvre
Based on the thinking of Pierre Bourdieu on the objectification of objectifying position, we will examine in this article the unthought and assumptions that were ours in conducting a research on teaching practices. After recalling the positioning of Bourdieu reflective analysis practical knowledge, we will present the protocol of a research conducted in one year with a teacher preparation course in order to analyze their teaching practices. We will question the assumptions of the theoretical framework of choice - in this case the "conceptualization in action" developed by Vergnaud - then those concerning the selection of a particular methodological device maintenance in a situation of self-confrontation. To participate in the opening of discussions on current sociological conditions of the scientific study of educational science education practices this test of self-analysis aims.